Trends of mutation accumulation across global SARS-CoV-2 genomes: Implications for the evolution of the novel coronavirus (2020)
To understand SARS-CoV-2 microevolution, this study explored the genome-wide frequency, gene-wise distribution, and molecular nature of all point-mutations detected across its 71703 RNA-genomes deposited in GISAID till 21 August 2020. Globally, nsp1/nsp2 and orf7a/orf3a were the most mutation-ridden non-structural and structural genes respectively. Phylogeny of 4618 spatiotemporally-representative genomes revealed that entities belonging to the early lineages are mostly spread over Asian countries, including India, whereas the recently-derived lineages are more globally distributed. Of the total 20163 instances of polymorphism detected across global genomes, 12594 and 7569 involved transitions and transversions, predominated by cytidine-to-uridine and guanosine-to-uridine conversions, respectively. Positive selection of nonsynonymous mutations (dN/dS >1) in most of the structural, but not the non-structural, genes indicated that SARS-CoV-2 has already harmonized its replication/transcription machineries with the host metabolism, while it is still redefining virulence/transmissibility strategies at the molecular level. Mechanistic bases and evolutionary/pathogenicity-related implications are discussed for the predominant mutation-types.